Persepsi terhadap perkhidmatan kaunseling dan hubungannya dengan masalah pekerja : satu tinjauan di perbadanan pembekalan letrik Sarawak (SESCO) - Ramilah, Boje. (2001)
The purpose of this study is aimed at identifying employees' problems and their perception towards counseling services at the work place. They were 54 employees involved in the study. Questionnaires based on Likert Scale were administered to the employees for the purpose of data collection.